2016
DOI: 10.1097/won.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Web-Based Self-management Intervention for Intermittent Urinary Catheter Users With Spinal Cord Injury

Abstract: Purpose The purpose of this study was to evaluate the feasibility of a new web-based intermittent catheter self-management intervention. Design We tested the acceptability and usability of intervention components, which included multiple web-based materials (an online urinary diary adapted for mobile phone use and an educational booklet), three phone calls with a nurse, and a peer led discussion forum. Subjects and setting Thirty adults with spinal cord injury using an intermittent catheter for bladder dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…Structured social support was defined as any established system to check-in or provide support outside a traditional clinic setting. Two studies assessed the effects of telemedicine on UTI in NB with conflicting results: a 3-month study following 26 patients showed no UTI reduction after a telemedicine intervention ( 90 ). A study assessing 49 patients with NB found a significant reduction in UTI with telemedicine ( 91 ).…”
Section: Resultsmentioning
confidence: 99%
“…Structured social support was defined as any established system to check-in or provide support outside a traditional clinic setting. Two studies assessed the effects of telemedicine on UTI in NB with conflicting results: a 3-month study following 26 patients showed no UTI reduction after a telemedicine intervention ( 90 ). A study assessing 49 patients with NB found a significant reduction in UTI with telemedicine ( 91 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different aims and outcomes, and lack of information about selection criteria, different categories, and modalities, are weaknesses in the studies. As commented by Wilde et al [31], "because of the small the number of participants, small changes could not reach significance, even if there was a trend". These small sample sizes, makes it difficult to make any unified recommendations for the whole SCI population [31] or for further development.…”
Section: Discussionmentioning
confidence: 98%
“…[31][32][33]35]. In a pilot study [31] of a web-based self-management system for people with SCI utilizing intermittent catheterization (IC), 30 persons with SCI were enrolled, and 22 completed the entire program, which included three phone calls with a continence nurse and an online forum. The study also tested new selfefficacy-scales and self-management scales at the beginning and end of the study; however, they found no statistically significant improvement.…”
Section: Web-based Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving CBT‐PMPs online addresses transport and operational barriers to implementation, reduces costs of programme delivery and increases the participant's autonomy in completing the programme at their own pace and preferred times (Griffiths, Lindenmeyer, Powell, Lowe, & Thorogood, ; Nguyen, Carrieri‐Kohlman, Rankin, Slaughter, & Stulbarg, ; Perry et al, ). While this mode of delivery has shown promising results for addressing depression, mood disorders and catheter management in SCI (Migliorini, Sinclair, Brown, Tonge, & New, ; Verwer, Leeuwen, Bolier, & Post, ; Wilde et al, ), it has yet to be undertaken for SCI specific CBT‐PMPs. Hence this RCT was undertaken to test the efficacy of Spinal Cord Injury Pain Ireland (SPIRE) pain management programme, an internet‐delivered CBT‐PMP for SCI pain.…”
Section: Introductionmentioning
confidence: 99%